2001
DOI: 10.1046/j.1365-2923.2001.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching sexual history taking to health care professionals in primary care

Abstract: The overall quality of the courses was rated by participants, on average, at 89.95 (maximum 100), and the relevance of the topic at 91.40. Free text comments centred on the power of the training as a consciousness raiser, on the need to alter communication strategies, the need to change existing clinical practice and the value of role play as a methodology. Interactive courses on sexual health are highly acceptable to participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 14 publications
2
55
0
1
Order By: Relevance
“…Skelton and Matthews (2001) reported specifically on teaching the sexual history in ( postgraduate) primary care, and while other periodic references exist (Wenrich et al 1997), the work is not prolific. TempleSmith et al (1999) reported on attitudes to sexual history taking in GP, with focus on working practises.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Skelton and Matthews (2001) reported specifically on teaching the sexual history in ( postgraduate) primary care, and while other periodic references exist (Wenrich et al 1997), the work is not prolific. TempleSmith et al (1999) reported on attitudes to sexual history taking in GP, with focus on working practises.…”
Section: Practice Pointsmentioning
confidence: 99%
“…When patient SH is in question, "obtaining a history" is the most important method to establish an accurate finding (18). In the present study, the most frequent method for diagnosing an STI or SD was "obtaining a history", followed by "physical examination" and "diagnostic tests."…”
Section: Discussionmentioning
confidence: 63%
“…It is clear that sexuality is a meaningful part of early adult women's lives; however, few medical professionals ever ask about sex during office visits, citing concerns about time, embarrassment, and being ill-equipped to answer specific questions (Nusbaum et al 2002;Skelton and Matthews 2001). In turn, many individuals do not initiate sexual conversations with their doctors (Sadovsky and Nusbaum 2006).…”
Section: Implications For Policy and Researchmentioning
confidence: 99%